(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This comprehensive study explores the lexical and semantic dimensions of politeness in the speech cultures of Uzbek and English languages. By employing a combination of theoretical frameworks, including Brown and Levinson’s Politeness Theory and Speech Act Theory, the research analyzes how politeness is linguistically structured and culturally contextualized in both languages.